High‐Efficiency Organic Photovoltaic Cells Based on the Solution‐Processable Hole Transporting Interlayer Copper Thiocyanate (CuSCN) as a Replacement for PEDOT:PSS. Issue 3 (25th September 2014) - Yaacobi‐Gross, Nir; Treat, Neil D.; Pattanasattayavong, Pichaya; Faber, Hendrik; Perumal, Ajay K.; Stingelin, Natalie; Bradley, Donal D. C.; Stavrinou, Paul N.; Heeney, Martin; Anthopoulos, Thomas D.
<x xml:space="preserve">Abstract</x> The use of copper thiocyanate (CuSCN) as a universal solution‐processable and highly transparent hole‐transporting layer in organic bulk‐heterojunction photovoltaic cells is demonstrated. When CuSCN is employed as a replacement for the commonly used poly(3, 4‐ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS), organic solar cells with maximum power conversion efficiency of 8%, are realized; this value is 1.27 times higher than that for optimized control cells based on PEDOT:PSS. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>